STRATEGI PENGELOLAAN SDM YANG TERINTEGRASI DALAM MENGHADAPI PERUBAHAN LINGKUNGAN GLOBAL - Widayanti, Rochmi (Manajemen Bisnis Syariah, 2012)
Human  resources  planning  is  a  management  process  in  determining organizational  human  resources  movement  fr om  the  exiting  position  to  expected position  in  the  futur e,  on  the  other  hand,  human  resources  strategy  is  unity  of  process and  activity  wich  is  done  toghether  among  HRD  Manager  and  line  managers.The  purpose  of  HR  integration  is  to  create  HR  demand  prediction  process wichh emerges fr om strategic and operational planning quantitatively compared to HR  supply  or  available  fr om  HR  existing  programs.Further more HR planning to be integrated with the specific strategy so that the  goal  can  be  achieved  effectively .Keywords  :  human  resources,  strategy ,  change,  global  environment